Remote sensing-derived time series of transient glacier snowline altitudes for High Mountain Asia, 1985–2021 - David Loibl; Niklas Richter; Inge Grünberg (Scientific Data)
Abstract This study presents a new dataset of remote sensing-derived Transient Snowline Altitude (TSLA) measurements for glaciers in High Mountain Asia. We use the Google Earth Engine to obtain TSLA data for approx. 2.8 · 104 glaciers larger than 0.5 km2. After filtering and postprocessing, the dataset comprises ca. 9.66 million TSLA measurements with an average of 341 ± 160 measurements per glacier, covering the time span 1985 to 2021.